The range of non-traditional anthropometric parameters to define obesity and obesity-related disease in children: a systematic review - Ranasinghe, Priyanga; Jayawardena, Ranil; Gamage, Nishadi; Pujitha Wickramasinghe, V; Hills, Andrew P (European journal of clinical nutrition, 2021)
Obesity is defined as an abnormal/excessive accumulation of body fat, associated with health consequences. Although overall obesity does confer a significant threat to the health of individuals, the distribution of body fat, especially abdominal/central obesity is of greater importance. For practical reasons, proxy anthropometric measurements have been developed to identify central obesity, however, major limitations are noted in these traditional measurements. The present study aims to evaluate the literature, to identify and describe non-traditional anthropometric measurements of overweight and obesity in children. The current systematic review was conducted in accordance with the PRISMA guidelines, and the search was undertaken in the PubMed database, using MeSH (Medical Subject Headings) terms. Data extracted from each study were: (a) details of the study, (b) anthropometric parameter(s) evaluated in the study and its details, (c) study methods, (d) objectives of the study and/or comparisons, and (e) main findings/conclusions of the study. The search yielded a total of 3697 articles, of which 31 studies were deemed eligible to be included. The literature search identified 13 non-traditional anthropometric parameters. Data on non-traditional anthropometric parameters were derived from 24 countries. Majority were descriptive cross-sectional studies (n = 29), while sample size varied from 65 to 23,043. Non-traditional anthropometric parameters showed variable correlation with obesity and/or related metabolic risk factors. Some parameters involved complex calculations, while others were based on a single anthropometric measurement or derived from traditional measures. Most studies lacked comparison with a 'gold standard' assessment of body fat, hence further research is required to determine their accuracy and precision.